Evaluating The Impact Of Innovative Assignment Design On Student Engagement And Learning Outcomes In Higher Education - Nuraziza Aliah; Andi Suwarni; Nurasia Natsir (FKIP, Universitas Palangka Raya, 2024)
This research explores the role of innovative assignment design in enhancing student engagement and learning outcomes within the context of higher education. Utilizing a mixed-methods approach, the study combines quantitative data from surveys of 120 students and 15 instructors of STIA Yappi Makassar across multiple institutions with qualitative insights from semi-structured interviews with a selected subset of these participants. The findings reveal a significant positive correlation between innovative assignment design and increased student engagement, as well as improved learning outcomes. Quantitatively, students exposed to innovative assignments reported higher engagement levels and better learning outcomes compared to their peers in traditional assignment settings. Qualitatively, themes emerged highlighting the benefits of practical application and relevance found in innovative assignments, alongside challenges such as the need for clearer guidelines and additional support. This study underscores the potential of innovative pedagogical strategies to create more engaging, relevant, and effective learning environments in higher education. It calls for educators to embrace and refine these approaches, addressing implementation challenges to fully realize their benefits. The research contributes to the broader discourse on educational quality and innovation, offering evidence-based recommendations for enhancing student engagement and success through pedagogical innovation.